Fresno County Bar Association's Annual Judges' Dinner at Bob Crossland's Barn - Watkins, Howard::::::::: (1982)
Band playing: drums, Robert Oliver on trumpet, Truman Campbell on clarinet, Bernard Witkin watching, trombone, piano player